2021
DOI: 10.3390/ijerph18105488
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Orthorexia Nervosa and Its Diagnostic Tools—A Literature Review

Abstract: The aim of this article is to present the up-to-date diagnostic tools of orthorexia and markers of its prevalence on the basis of the available literature. The authors searched PubMedCentral (PMC) and Google Scholar with the search entry of “orthorexia”, “orthorexia nervosa”, and “orthorexicbehaviours”. We describe the tools of evaluation of orthorexicbehaviour (i.e., orthorexia self-test—BOT, the ORTO-15 questionnaire, Eating Habits Questionnaire—EHQ, Düsseldorf Orthorexia Scale—DOS, Teruel Orthorexia Scale—T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 118 publications
(176 reference statements)
4
82
1
1
Order By: Relevance
“…A characteristic of ON is a gradual intensification of dietary restrictions, often paired with obsessive thoughts and deviations from the imposed norms, leading to intense feelings of guilt, fear, shame, and additional dietary restrictions [41,65]. In the studies included herein, ON tendencies were associated with an increased fiber intake and a lower energy consumption.…”
Section: Characteristics Of Patients With Dm and On Tendenciesmentioning
confidence: 87%
See 1 more Smart Citation
“…A characteristic of ON is a gradual intensification of dietary restrictions, often paired with obsessive thoughts and deviations from the imposed norms, leading to intense feelings of guilt, fear, shame, and additional dietary restrictions [41,65]. In the studies included herein, ON tendencies were associated with an increased fiber intake and a lower energy consumption.…”
Section: Characteristics Of Patients With Dm and On Tendenciesmentioning
confidence: 87%
“…Despite the plethora of tools used to identify ON [41], most studies relied on the ORTO-15 or its adaptations, as seen in research on the general population [42]. Specifically, one study used the ORTO-15 [36]; two studies used the Turkish adaptation of the ORTO-15 (ORTO-11) [35,38]; and Fidan [34] and Anil [37] used the ORTHO-11 and OR-THO-15, respectively-probably misspelt variations of the ORTO-15 tool.…”
Section: Tools Used To Identify On Tendenciesmentioning
confidence: 99%
“…The prevalence of orthorexia depends on the diagnostic cut-off criteria, the instrument used, or geographic region, and ranges between 1% to 89%, as suggested by review studies [43][44][45]. However, Varga et al [45] found the average prevalence of ON to be 6.9% in the general population, while rates between 1% and 7% were estimated by using Düseldorf Orthorexia Scale (DOS ≥ 30) [46], and 5.5% using Test of Orthorexia Nervosa (TON-17 ≥ 61) [47] in the Polish sample.…”
Section: Orthorexia Nervosamentioning
confidence: 99%
“…The prevalence of ON was previously discussed as challenging to compare with other studies since various measurement tools have different cut-off criteria. Cross-cultural differences may also be important for it [43][44][45]. Di Renzo et al [14] examined the impact of the early stage of the COVID-19 pandemic on eating habits and lifestyle changes among the Italian population.…”
Section: Orthorexia Fear Of Covid-19 and Pa Among University Studentsmentioning
confidence: 99%
“…To date, advancement in knowledge about OrNe has been, to a certain extent, hindered by the way orthorexia was assessed. Multiple scales have been used to screen for orthorexic tendencies and behaviors among people: orthorexia self-test (BOT), the ORTO-15 questionnaire, Eating Habits Questionnaire (EHQ), Düsseldorf Orthorexia Scale (DOS), Teruel Orthorexia Scale (TOS), Barcelona Orthorexia Scale (BOS), and Orthorexia Nervosa Inventory (ONI) [ 22 ]. The most commonly used scale, the ORTO-15 tool [ 2 , 3 ], was created and validated in Italy [ 23 ].…”
Section: Introductionmentioning
confidence: 99%